Measurement scale influences in the evaluation of sight‐word reading interventions. Issue 2 (25th April 2014) - Yaw, Jared; Skinner, Christopher H.; Delisle, Jean; Skinner, Amy L.; Maurer, Kristin; Cihak, David; Wilhoit, Brian; Booher, Joshua
<x xml:space="preserve">Abstract</x> Working with elementary students with disabilities, we used alternating treatment designs to evaluate and compare the effects of 2 computer‐based flash card sight‐word reading interventions, 1 with 1‐s response intervals and another with 5‐s response intervals. In Study 1, we held instructional time constant, applying both interventions for 3 min. Although students completed 6 learning trials per word during each 1‐s session and 2 trials per word during each 5‐s session, results showed similar acquisition rates for 1‐s and 5‐s words. During Study 2, we held learning trials constant (3 per word) and allowed instructional time to vary. When we measured learning using cumulative instructional sessions, the interventions appeared to cause similar increases in acquisition rates. When the same learning data were measured and plotted using cumulative instructional seconds, all participants showed greater learning rates under the 1‐s intervention. Discussion focuses on how measurement scales can influence comparative effectiveness studies.